Dynamic assembly of DNA and polylysine mediated by electric energy. Issue 8 (11th December 2014) - Niu, Lin; Yang, Xuyan; Zhu, Xiaocui; Yin, Yudan; Qu, Wei; Zhou, Jihan; Zhao, Meiping; Liang, Dehai
Abstract : Under an electric field, the complex of DNA and PLL ejects daughter vehicles with mobility three times faster than free DNA. Abstract : Under an electric field, the complexes formed by DNA and polylysine exhibit novel features, such as selective merging of particles, ejecting of daughter vehicles, and differentiation of particles of varying mobility. The mobility of the complex could be three times faster than that of free DNA.